2023
DOI: 10.1002/ange.202214707
|View full text |Cite
|
Sign up to set email alerts
|

Metal–Organic Frameworks as Electrocatalysts

Abstract: Transition metal complexes are well-known homogeneous electrocatalysts. In this regard, metal-organic frameworks (MOFs) can be considered as an ensemble of transition metal complexes ordered in a periodic arrangement. In addition, MOFs have several additional positive structural features that make them suitable for electrocatalysis, including large surface area, high porosity, and high content of accessible transition metal with exchangeable coordination positions. The present review describes the current stat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 131 publications
(135 reference statements)
0
12
0
Order By: Relevance
“…The solid-state NMR spectra were acquired at 18.8 T / 800 MHz spectrometer equipped with a Bruker Avance Neo console. The cross polarization (CP) contact time used in the 1 H- 13 C heteronuclear correlation (HETCOR) and 7 Li-1 H CP-heteronuclear singlequantum coherence (HSQC) [35] experiments are 2.5 ms and 200 µs, respectively. We have implemented frequency switched Lee-Goldburg (FSLG) homonuclear 1 H decoupling during the 1 H evolution period to achieve narrower lines in HETCOR [36].…”
Section: Solid-state Nmrmentioning
confidence: 99%
See 1 more Smart Citation
“…The solid-state NMR spectra were acquired at 18.8 T / 800 MHz spectrometer equipped with a Bruker Avance Neo console. The cross polarization (CP) contact time used in the 1 H- 13 C heteronuclear correlation (HETCOR) and 7 Li-1 H CP-heteronuclear singlequantum coherence (HSQC) [35] experiments are 2.5 ms and 200 µs, respectively. We have implemented frequency switched Lee-Goldburg (FSLG) homonuclear 1 H decoupling during the 1 H evolution period to achieve narrower lines in HETCOR [36].…”
Section: Solid-state Nmrmentioning
confidence: 99%
“…Metal-Organic Frameworks (MOFs) are one of the latest classes of ordered micro-or mesoporous hybrid materials with highly tunable structural and/or chemical characteristics suitable for a wide range of applications from gas sorption, separation, catalysis, sensing to biomedicine, among others [13][14][15][16]. This makes them highly promising candidates to limit polysulfides migration due to their unique structural and chemical properties, such as high porosity, uniform and tunable pore size, Lewis/Bronsted acidity, and structural defects, which shall significantly impact their molecular sieving ability [17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…Over the past decade, metal–organic frameworks (MOFs) have been widely studied as an emerging class of crystalline porous framework materials with a large specific surface area, ultrahigh porosity, tunable pore sizes, chemical components, and morphology. Furthermore, due to the abundance of well-dispersed metal active sites, MOFs have received intensively increasing attention as a promising platform for electrocatalytic applications. Unfortunately, due to poor electrical conductivity, pristine MOFs’ electrocatalytic activities and durability are unsatisfactory for large-scale applications. , To further improve the activity, rational modification of the components of the MOFs and their hybridization with conductive materials such as conductive polymers and graphene have been demonstrated as a prospective strategy. , In this context, the electronic properties of the well-dispersed metal active sites can be altered by incorporating the foreign metals into the MOF matrix. However, to the best of our knowledge, no studies have been reported on multimetallic-based MOFs for electrochemical seawater electrolysis.…”
Section: Introductionmentioning
confidence: 99%
“…11 Some of the reactions studied in energy conversion devices that convert electrical energy to chemical energy are the hydrogen evolution reaction (HER) and oxygen evolution reaction (OER) in water electrolyzers, the CO 2 reduction reaction (CO 2 RR) in bicarbonate/carbonate electrolyzers, and the nitrogen reduction reaction (NRR) in nitrogen electrochemical fixation devices. [12][13][14] On the other hand, we have the oxygen reduction reaction (ORR) and hydrogen oxidation reaction (HOR) in H 2 -O 2 fuel cells and the oxidation reactions of small molecules like methanol, glucose, urea, polysulfide, and hydrazine (hence, MOR, GOR, UOR, SOR, HzOR) in their respective direct-fuel-O 2 fuel cells. [15][16][17] These small molecule oxidation reactions are also now used for masking the highly energy demanding OER of water electrolysis so that the energy efficiency of H 2 production from water can be improved.…”
Section: Introductionmentioning
confidence: 99%